'The digital is everywhere': Negotiating the aesthetics of digital mediation in Montreal's electroacoustic and sound art scenes - Valiquet, Patrick Joseph (Université d'Oxford, 2014)
In this thesis I argue that the relationship between the increasing ubiquity of digital audio technologies and the transformation of aesthetic hierarchies in electroacoustic and sound art traditions is not deterministic, but negotiated by producers and policy-makers in specific historical and cultural contexts. Interviews, observations, and historical data were gathered during sixteen months of ethnographic fieldwork in the Canadian city of Montreal between 2011 and 2012. Research was conducted and analysed in collaboration with a transnational group of researchers on a programme of comparative research that tracked global changes to music and musical practice associated with digital technologies. The introduction presents Montreal as a rich ecology in which to track struggles for aesthetic authority, detailing its history as a key site of electroacoustic and sound art production, and its local positioning as a politically strategic 'hub' for the Canadian culture industry. Core chapters examine the specific role of digital mediation in the negotiation of electroacoustic and sound art aesthetics from multiple interlocking perspectives: the recursive relationship between technological affordances and theories of mediation; the mobilisation of digital technologies in the delineation of cultural, professional and generational territories; the political contestation of digital literacies and pedagogies; the articulation of the digital's opposition with analogue in the construction of instruments and recording formats; and the effects of the digital on the dynamics of genre and genre hierarchies. The concluding chapter offers a critique of the notion that digital mediation has shifted the balance between the normative and the generative dimensions of genrefication in the scenes in question, and closes by suggesting how a better understanding of this shift at an empirical level can inform an ongoing rethinking of the interaction between technology and aesthetics among scholars, policy makers, and musicians.